Language and meaning in the age of modernism C.K. Ogden and his contemporaries - McElvenny, James ca. 20./21. Jh (Edinburgh University Press, 2018)
This book explores the influential currents in the philosophy of language and linguistics of the first half of the twentieth century, from the perspective of the English scholar C. K. Ogden (1889-1957). It reveals links between early analytic philosophy, semiotics and linguistics in a crucial period of their respective histories